Model Inovasi Sosial Berbasis Maqāṣid al-Syarī‘ah pada Majelis Ta’lim An Nuriyah Bajawa, Nusa Tenggara Timur - Nina Agustina Fajriah; Luhur Prasetiyo; Ely Masykuroh (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to examine the social innovation model based on maqāṣid syarī‘ah that developed in the Majelis Ta’lim An Nuriyah Bajawa as a form of empowerment of the minority Muslim community. The approach used is qualitative with a case study type through in-depth interviews. The results of the study indicate that the Majelis Ta’lim An Nuriyah becomes a space for the formation of social innovation integrated with the values ​​of maqāṣid syarī‘ah, including ḥifẓ al-dīn (protection of religion) through routine Islamic studies and education; ḥifẓ al-nafs (protection of the soul) through social activities and charity; ḥifẓ al-‘aql (protection of reason) through business digitalization training; ḥifẓ al-nasl (protection of offspring) through Islamic family education; and ḥifẓ al-māl (protection of wealth) through management of congregational funds based on sincerity and social benefits. The emerging social innovation is rooted in the spirit of togetherness, tolerance, and women's independence, while also reflecting the transformation of Islamic values ​​in a pluralistic and dynamic social context. These findings enrich the literature on the integration of the maqāṣid shari'ah (Islamic principles) into faith-based community empowerment practices and offer a conceptual model of Islamic social innovation relevant to minority communities.